1996
DOI: 10.21273/jashs.121.4.649
|View full text |Cite
|
Sign up to set email alerts
|

Root Restriction and Potassium and Calcium Solution Concentrations Affect Dry-matter Production, Cation Uptake, and Blossom-end Rot in Greenhouse Tomato

Abstract: Root restriction has been reported to reduce fruit yield, the incidence of blossom end rot (BER) and K concentration in tomato (Lycopersicon esculentum L. `F121') plant organs. The objectives of the present work were to study the effect of root restriction, and combination of K and Ca solution concentrations, on greenhouse tomato fruit yield, quality and cation uptake. Root restriction reduced total yield but improved fruit quality by increasing the dry matter concentration a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 20 publications
5
21
0
Order By: Relevance
“…In the study of Bar-Tal and Pressman (1996) in the aero-hydroponics system, root restriction decreased Ca uptake rate per plant, but there was a trend of increasing F Ca when root restriction was combined with low K concentration, which is consistent with the ability of the restricted-root plants to maintain Ca concentrations in plant organs similar to those in non-restricted plants. Choi et al (1997) reported that root restriction by small containers (190 ml) strongly suppressed transport of 45 Ca ions to new leaves and apices relative to the plants in the control containers (20 L).…”
Section: The Effects Of Restricted Root Volume On Plant Nutritionsupporting
confidence: 58%
See 2 more Smart Citations
“…In the study of Bar-Tal and Pressman (1996) in the aero-hydroponics system, root restriction decreased Ca uptake rate per plant, but there was a trend of increasing F Ca when root restriction was combined with low K concentration, which is consistent with the ability of the restricted-root plants to maintain Ca concentrations in plant organs similar to those in non-restricted plants. Choi et al (1997) reported that root restriction by small containers (190 ml) strongly suppressed transport of 45 Ca ions to new leaves and apices relative to the plants in the control containers (20 L).…”
Section: The Effects Of Restricted Root Volume On Plant Nutritionsupporting
confidence: 58%
“…But even constant supply (as is practical in closed systems) cannot overcome all the constraints posed by small root volume, as discussed in Chap. 9, and by Bar-Tal et al (1990, Bar-Tal and Pressman (1996) and Rieger and Marra (1994). It is therefore important to select the appropriate container size for each specific crop, based on its growth rate and final desired size and growing conditions.…”
Section: The Effects Of Restricted Root Volume On Plant Nutritionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Bar-Tal and Pressman (1996) found that the incidence of BER correlated better with the K:Ca ratio in the leaves than with the K:Ca ratio in the fruits. Nevertheless, a significant antagonistic effect of K on Ca uptake has frequently been observed in hydroponically grown tomatoes; for instance, an increase in K concentration in the nutrient solution often reduces Ca uptake, thus increasing the risk of BER development (Bar-Tal and Pressman, 1996; Wada et al ., 1996; Taylor et al ., 2004). Besides the K:Ca ratio, here we also found that the Mg:Ca ratio in the fruit positively correlated with BER incidence (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Root growth restricted plants produced higher soluble sugars content of strawberry fruits (39), and increased the fruit DW concentration of tomato (40). Root growth restricted plants produced higher soluble sugars content of strawberry fruits (39), and increased the fruit DW concentration of tomato (40).…”
Section: Xu Wolf and Kafkafimentioning
confidence: 98%